ECHOCARDIOGRAPHY IN RIGHT VENTRICULAR MYOCARDIAL INFARCTION - H. G. Hayrapetyan; K. G. Adamyan (Кардиоваскулярная терапия и профилактика, 2013)
This paper presents the views on two-dimensional (2D) echocardiography (EchoCG) in the assessment of right ventricular (RV) structure and function. In order to quantitatively assess the RV global function, the following parameters can be used: RV outflow tract shortening fraction, RV fractional area change, tricuspid annular plane systolic excursion, and Tei index. For these parameters, their assessment methods, as well as their strengths and limitations, are discussed.